Grassroots Death Sentences? The Social Movment for Capital Child Rape Laws - Bell, Monica C (2008)
Despite the Supreme Court's 1977 ruling in Coker v. Georgia declaring use of the death penalty for rape unconstitutional, there has been a recent explosion of state statutes making the death penalty available for the rape of a child. Numerous articles have tried to discern whether using the death penalty for child rape comports with the Coker holding-often reaching divergent conclusions-but none has focused first on the socio-political setting that brought about these laws to inform their constitutional analysis. This Article attempts to begin contextualizing capital child rape statutes within a social movements framework. I argue that capital child rape statutes can be attributed to three movements: the popular movement to shame, fear, and isolate sex offenders; the feminist movement for harsher punishment of sexual and intra-familial violence; and the legal and political movement to punish attacks against vulnerable victims with death. Understanding these statutes in a richer way helps shed light on their potential constitutional problems